Morphological Audit of glomerular diseases in a tertiary care Hospital. - Shafique, Maria; Bukhari, Uzma; Kumar, Suresh; George, Anita; Bukhari, Asma; Sajjad, Mehwish (International Journal of Endorsing Health Science Research, 2022)
Background: Glomerular diseases are a universal health issue, and Pakistan ranks eighth in renal disease, causing 20,000 deaths every year. Renal biopsy is a valuable diagnostic tool and provides prognostic insight and therapeutic plans. The study's objective is to determine the frequency and pattern of various glomerulopathies concerning age and gender. Methodology: A cross-sectional study was performed at the Department of Pathology, Ziauddin Medical University, and Hospital, Karachi, from 19th December 2018 to 15th April 2019. A total of 91 patients were included of either gender with a clinical history of glomerulonephritis. All biopsy samples were analyzed by using light and immunofluorescence microscopy techniques. Patient data were compiled and analyzed through SPSS version 20.0. Results: A total of 91 cases of the renal biopsy were evaluated; 51.6% of these cases were male patients. Forty-nine (53.8%) cases were reported as focal segmental glomerulosclerosis, 35(38.5%) were diagnosed with membranous glomerulonephritis, and 7(7.7%) were reported as mesangiocapillary glomerulonephritis. In membranous glomerulonephritis, 7.7% were pre-spike membranous glomerulonephritis. In the current study, 35.2% of cases showed diffuse glomerular basement membrane (GBM) thickening with spikes, and 4.4% showed GBM thickening with focal spikes on silver stain. Conclusion: Glomerular diseases are slightly more prevalent in males than females. The most commonly diagnosed primary glomerulonephritis was focal segmental glomerulosclerosis, followed by membranous glomerulonephritis.